First report of warble fly infestation in markhor, Capra falconeri - Ángeles Sáez-Ventura; Gracia M. Liébanas; Antonio Sánchez; Ismoil Kholmatov; Stéphane Ostrowski; Jesús M. Pérez (International Journal for Parasitology: Parasites and Wildlife)
In December 2023, 35 third-instar larvae were collected from subcutaneous granulomatous cysts in a free-ranging markhor (Capra falconeri) hunted in the Dashtijum region of the Khazratishoh mountain range, Tajikistan. The larvae were identified as those of Przhevalskiana silenus (Diptera: Oestridae: Hypodermatinae). To the best of our knowledge, this is the first report of an oestrid fly infestation in this host species.